2011
DOI: 10.1016/j.bcp.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

From differential induction of UDP-glucuronosyltransferases in rat liver to characterization of responsible ligand-activated transcription factors, and their multilevel crosstalk in humans

Abstract: . From differential induction of UDP-glucuronosyltransferases in rat liver to characterization of responsible ligand-activated transcription factors, and their multilevel crosstalk in humans. Biochemical Pharmacology, Elsevier, 2011, 82 (1) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…In agreement with our findings, previous studies have also shown that As(III) decreases dexamethasone-mediated induction of CYP3A23 mRNA, protein, and catalytic activity in primary rat hepatocytes (Jacobs et al, 1999). However, these studies used dexamethasone, which primarily induces the glucocorticoid receptor, rather than PXR (Bock, 2011).…”
Section: Inhibition Of Cytochrome P450s By As(iii)supporting
confidence: 92%
“…In agreement with our findings, previous studies have also shown that As(III) decreases dexamethasone-mediated induction of CYP3A23 mRNA, protein, and catalytic activity in primary rat hepatocytes (Jacobs et al, 1999). However, these studies used dexamethasone, which primarily induces the glucocorticoid receptor, rather than PXR (Bock, 2011).…”
Section: Inhibition Of Cytochrome P450s By As(iii)supporting
confidence: 92%
“…A number of nuclear receptors, including PXR, constitute androstane receptor (CAR), peroxisome proliferator-activated receptor α , retinoid X receptor, and AhR, and transcriptional factors, including nuclear factor-erythroid 2-related factor 2 (Nrf2) and activating protein 1 (AP-1), have been shown to play an important role in the transcription of genes encoding drug-metabolizing enzymes and transporters [39]. For instance, activation of Nrf2, AhR, PXR, and CAR upregulates the transcription of UGT and GST in a coordinated manner [40, 41]. AhR is the key mediator of 2,3,7,8-tetrachlorodibenzo-p-dioxin-induced changes in CYP1A genes [42].…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are required for detoxification of electrophilic compounds by reaction with glutathione [50]. UGTs also contribute to the antioxidant response by catalyzing conjugation of glucuronic acid, for instance, with quinols, thereby facilitating their excretion [51]. Interestingly, some ligands are able to differentially activate the AhR/Nrf2/NQO1 pathway while the AhR/CYP1A1 axis is only weakly induced.…”
Section: The Ahr-nrf2 Pathwaymentioning
confidence: 99%